1992
DOI: 10.1111/j.1442-200x.1992.tb00972.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology of HTLV‐I‐Associated Myelopathy—A Report of Two Autopsy Cases—

Abstract: A neuropathological analysis was performed in two autopsy cases of HTLV‐I‐associated myelopathy. The thoracic spinal cords were most severely affected and the histopathological findings consisted of mononuclear cell infiltration, marked destruction of myelin and axons and astrocytic gliosis. More than half the infiltrated cells were positive for pan‐T cell marker; B cells were sparse in the parenchyma and subarachnoid spaces. CD4 and CD8 positive cells were found in the early stages of the lesions. CD8, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…In some HLA-A*201 HAM/ TSP patients, the frequency of Tax11-19-specific CTLs can be as high as 30% of total CD8 + T cells in peripheral blood (10) and even higher in cerebrospinal fluid (6). Neuropathological findings have demonstrated focal infiltrates of T cells and macrophages in the CNS (11). These observations have suggested that inflammatory T cells (particularly virus-specific CD8 + CTLs) may play an immunopathologic role in this disorder.…”
Section: Introductionmentioning
confidence: 77%
“…In some HLA-A*201 HAM/ TSP patients, the frequency of Tax11-19-specific CTLs can be as high as 30% of total CD8 + T cells in peripheral blood (10) and even higher in cerebrospinal fluid (6). Neuropathological findings have demonstrated focal infiltrates of T cells and macrophages in the CNS (11). These observations have suggested that inflammatory T cells (particularly virus-specific CD8 + CTLs) may play an immunopathologic role in this disorder.…”
Section: Introductionmentioning
confidence: 77%
“…Although cognitive impairment is included in less common neurological findings in this disease (Osame and McArthur, 1992), several necropsy studies have revealed that the critical pathological findings including mononuclear infiltration or perivascular cuffing, which is prominent in the thoracic spinal cord, are commonly seen in the cerebral white matter of HAM/TSP patients (Izumo et al, 1989). Cerebral white matter involvement detected by magnetic resonance imaging (MRI) has been reported in an HTLV-I infected symptomless individual (Mattson et al, 1987) and the incidence of cerebral MRI abnormalities is significantly higher in patients with HAM/TSP than in the controls (Kira et al, 1988;Furukawa et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…There are around 34 autopsied TSP/HAM cases described in the world [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . This number of cases is limited, since León et al 18 , in a world meta-analytical analysis, reported on 1261 cases of TSP/HAM.…”
Section: V-i (Pet/mah) De Longa Evolução -I (Pet/mah) De Longa Evoluçmentioning
confidence: 99%